The impact of community health workers on antenatal and infant health in India: A cross-sectional study - Pranay Nadella; S.V. Subramanian; Andres Roman-Urrestarazu (SSM - Population Health, 2021)
Community health workers (CHWs) are central to India's strategy for reaching the Sustainable Development Goals around maternal and child health. Despite India's significant investment in these programs, few studies have analyzed the effect of CHWs across India.
Keywords: Primary health; Mitanin; Community health